Abuse of power in public office - Yamani, Ali Muhammad; Sayed, Aladdin Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at raise awareness of the concept of abuse of power, and the role of judicial oversight over it, statement of judicial guarantees for individuals against abuse of power, explanation of the importance of judicial decisions fulfilling their pillars, clarify penalties and sanctions that might fall on the perpetrator of abuse of power, and statement of the implications of abuse of power.In order for this study to achieve its objectives, the inductive method was used, which depends on the extrapolation of the study problem through the study literature, books and literature in this field in proportion to this type of studies.Among the most important results of the study: The defect of abuse of power can be defined as: (the abuse of power committed in a legal framework, but with the aim of reaching illegal goals), there is a great convergence in the two legislative texts that were mentioned in the Saudi system and the Egyptian State Council Law, rather, it can be said that there is an almost identicalness between the two texts, as if the Saudi regulator had quoted the text of the system from the Egyptian law, there is a controversy in the relationship between the defect of abuse of power and the defect of lack of competence, and the necessity of applying Islamic Sharia in the Saudi system, and this results in achieving the principle of legitimacy in its best form, as the relationship between judicial oversight and the principle of legitimacy depends on an independent judiciary.The study concluded with a set of recommendations and procedures to minimize abuse-of-power events as follows. Employees shall be trained upon granting them the powers to issue decisions. Litigation procedures shall be simplified. The competent court shall make rulings independently (to be of the public order). Punishment shall be applied so that the infarction is decisively proven and proportionate to the offense committed.
Keywords: abuse of power; judicial oversight; penalties; elements of judicial decisions